Functionalized 1,3,5-triazine-derivatives as promising anticancer agents: synthesis and cytotoxic activity in vitro - A. V. Protas; O. V. Mikolaichuk; E. A. Popova; K. V. Timoshchuk; D. N. Maistrenko; O. E. Molchanov; V. V. Sharoyko; K. N. Semenov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
Introduction. A promising area of application of 1,3,5-triazines in medical chemistry is the development of highly effective anticancer agents. It is noteworthy that a significant cytotoxic effect may occur with 2,4,6-substituted 1,3,5-triazine derivatives containing aziridine rings as substituents. These compounds interact with DNA molecules of tumor cells and they are alkylating agents.The objective was to synthesize and investigate the cytotoxic activity in vitro of new aziridine–containing 1,3,5-triazine derivatives against tumor cell lines of human lung adenocarcinoma A549 and human hepatocarcinoma Huh7 and to evaluate the effect of the length of the hydrocarbon radical in the dioxane cycle on the cytotoxic effect of the obtained compounds.Methods and materials. The synthesis of the 1,3,5-triazine derivatives was carried out using 2,4,6-trichloro-1,3,5-triazine (cyanuric chloride) as the starting reagent. The composition and structure of the obtained compounds were proven by elemental CHN analysis and 1H, 13C{1H} NMR spectroscopy. The cytotoxicity was studied using the MTT colorimetric assay.Results. Novel 1,3,5-triazine derivatives were synthesized and fully characterized: (5-((4-(aziridin-1-yl)-6-chloro-1,3,5triazin-2-yl)amino)-2-ethyl-2-methyl-1,3-dioxan-5-yl)methanol and (5-((4-(aziridin-1-yl)-6-chloro-1,3,5-triazin-2-yl)amino)2-isobutyl-2-methyl-1,3-dioxan-5-yl)methanol. Also, cytotoxic effect against tumor cell lines of human lung adenocarcinoma (A549) and human hepatocarcinoma (Huh7) was studied using the MTT assay. It has been shown that an increase in the length of hydrocarbon radicals in the dioxane ring at position C2 leads to a decrease in cytotoxic effect.Conclusion. The synthesized (5-((4-(aziridin-1-yl)-6-chloro-1,3,5-triazin-2-yl)amino)-2-ethyl-2-methyl-1,3-dioxane-5 -yl) methanol and (5-((4-(aziridin-1-yl)-6-chloro-1,3,5-triazin-2-yl)amino)-2-isobutyl-2-methyl-1,3-dioxan-5-yl)methanol cause a dose-dependent decrease against the survival of tumor cell lines A549 and Huh7.